Answer:
The difference is
Step-by-step explanation:
We must find the common denominator of the fractions.
The common denominator of and is ; therefore we have
now it is easy to subtract using the number line: we have to move units to the left in order to get to .
Thus our answer is
Answer: 7
Step-by-step explanation: 5 + 1 + 1 = 7 .
Answer:
16
Step-by-step explanation:
You have: 14 / (7/8)
To divide by fractions, all you have to do is take the reciprocal of the second number, aka flip it
so, if you do that, you get 14 * 8/7
14*8=112, and 112/7 is 16
Answer:
8x²- x -8
Step-by-step explanation:
The question is not well written. I guess what you mean is:
Subtract -2x^2+4x-1 ( minus 2x squared plus 4x minus 1) from 6x^2+3x-9 (6x squared plus 3x minus 9).
To subtract -2x^2+4x-1 from 6x^2+3x-9, that is
6x^2+3x-9 - (-2x^2+4x-1). This can be written as
6x²+3x-9 - (-2x²+4x-1)
Now, opening the bracket, we will get
6x²+3x-9 +2x²-4x+1
Then, collecting like terms, we get
6x²+2x²+3x-4x-9+1
6x²+2x² = 8x²
3x-4x = -x
-9+1 = -8
∴6x²+2x²+3x-4x-9+1 becomes
8x²-x -8
The answer is 8x²-x -8.
Answer:
B = 15
Step-by-step explanation:
<u>Combine multiplied terms into a single fraction</u>
6 + 2b/5 = 12
<u>Subtract 6 from both sides</u>
6 + 2b/5 <em>(-6)</em> = 12 <em>(-6) </em>= 2b/5 = 6
<u>Multiply all terms by the same value to eliminate fraction denominators</u>
2b/5 <em>( x 5) </em>= 6<em> (x 5)</em>
<em />
<u>Simplify</u>
2b = 30